Interactions between Immunosuppressive Therapy and Direct-Acting Antivirals in Kidney Transplant Recipient with Hepatitis C Infection - Paolo Carta; Federica Curci; Leonardo Caroti; Larti Aida; Lorenzo Di Maria; Lino Cirami (Journal of Renal and Hepatic Disorders)
Hepatitis C virus (HCV) causes increased mortality and morbidity in kidney transplant patients. Interferon-based therapies are poorly tolerated and involve the risk of rejection. The new direct-acting antiviral drugs (DAAs) have revolutionized the treatment of HCV infection in transplant patients. This observational study evaluates changes in immunosuppressive therapy during treatment with DAA in renal transplant recipients. In our transplant center, we selected seven HCV-positive patients at the time of transplantation , four men and three women, with an average age of 61 ± 7 years, in therapy with DAA. The dose and the blood levels of the immunosuppressive drugs were evaluated at the beginning and end of antiviral therapy, together with creatinine and proteinuria. Viremia was negativized in all patients within the initial 8 weeks of therapy. Currently, the number of patients is too limited to perform a sta-tistical analysis and obtain significant results. In one patient, the dose of Cyclosporine was lowered to 10 mg, while for the remaining patients it was not necessary to change the dose of immunosuppressive drugs. DAAs give encouraging results in the eradication of HCV in renal transplant recipients, although they are associated with potential adverse drug interactions. The preliminary data of our study suggest that it is not necessary to change the dose of immunosuppressive drugs during therapy and that creatinine and proteinuria remain stationary. We will achieve more significant results in the future, adding more patients to our study. However, further randomized trials are necessary to confirm the safety of DAAs.